2022
DOI: 10.1186/s13223-022-00650-w
|View full text |Cite
|
Sign up to set email alerts
|

The use of dupilumab in severe atopic dermatitis during pregnancy: a case report

Abstract: Background Atopic dermatitis is a common chronic skin disease that can occur in pregnancy. Current treatments include topical and systemic glucocorticoids and cyclosporine. Presently, the only biologic approved for atopic dermatitis is dupilumab with limited data available regarding its safety profile in pregnancy. Case presentation We report a case of severe atopic dermatitis treated safely with dupilumab with no adverse maternal or fetal outcomes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Upon follow-up, the infant continued to meet age-appropriate milestones. The patient did not suffer from another flare-up despite the discontinuation of treatment [ 19 ]. Mian et al also found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Upon follow-up, the infant continued to meet age-appropriate milestones. The patient did not suffer from another flare-up despite the discontinuation of treatment [ 19 ]. Mian et al also found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…30 There are several case reports and data from the European Medicines Agency 140,141 which have shown favourable outcomes with no signals for adverse fetal outcomes in patients treated with DUP during pregnancy. 127,[142][143][144] A study of a large global pharmacovigilance database found that no pregnancy, puerperium or perinatal adverse drug reactions were associated with the use of DUP based on 36 reports. 145 The ERS/TSANZ task force has classified DUP as possibly safe during pregnancy and lactation.…”
Section: Tuberculosis (Tb)mentioning
confidence: 99%
“…When exposed to a surrogate antibody against IL‐4Rα, there were no significant adverse morphological, functional or immunological developmental effects observed in the offspring of cynomolgus monkeys 30 . There are several case reports and data from the European Medicines Agency 140,141 which have shown favourable outcomes with no signals for adverse fetal outcomes in patients treated with DUP during pregnancy 127,142–144 . A study of a large global pharmacovigilance database found that no pregnancy, puerperium or perinatal adverse drug reactions were associated with the use of DUP based on 36 reports 145 .…”
Section: Data Summariesmentioning
confidence: 99%
“…17,18 Labs are required when a comprehensive history and physical examination have failed to resolve diagnostic uncertainty. 19 Physiological skin changes, skin illnesses influenced by pregnancy, and particular dermatoses of pregnancy are the three groups into which the dermatoses of pregnancy fall. Pregnancyrelated inflammatory dermatoses are categorized into four subgroups.…”
Section: Introductionmentioning
confidence: 99%